Management of mandibular osteomyelite in a pediatric patient: case report (Research, Society and Development, 2021)
Osteomyelitis is an acute or chronic inflammatory process in the medullary or cortical spaces of the bone. Most of it is caused by bacterial infection resulting in a lytic and expansive destruction of the involved bone, with suppuration and formation of bone sequestration. It is rare in pediatric patients and the prevalence is higher in male patients, with the mandible being the most affected bone. The objective of this work is to report a clinical case of a child with osteomyelitis, discussing the correct diagnosis, its surgical treatment and pharmacological protocol. Female patient, 11 years old, with enlarged volume in the left submandibular masticatory space after tooth extraction 36, with the presence of inflammatory signs. Radiographic examination showed an irregular radiolucent lesion compatible with bone sequestration, suggestive of osteomyelitis. Pharmacological protocol based on broad-spectrum antibiotic therapy was instituted and bone cleaning and curettage were surgically performed. It is known that osteomyelitis is a complication commonly associated with immunodepressed patients, but it can occasionally occur in healthy patients, and treatment and early diagnosis is fundamental, especially in pediatric patients, as it becomes a potential cause for more severe infectious conditions. and complex, being able to spread and reach noble structures like the cavernous sinuses, leading to death.